2009
DOI: 10.1029/2009jd011849
|View full text |Cite
|
Sign up to set email alerts
|

Methane efflux from bubbles suspended in ice‐covered lakes in Syowa Oasis, East Antarctica

Abstract: [1] This is the first estimation of methane efflux from bubbles in lake ice in Antarctica. Bubbles suspended in shallow ice in 20 lakes were observed as part of the operations of the 45th Japanese Antarctic Research Expedition in ice-free rocky areas along the eastern coast of Lützow-Holm Bay (Syowa Oasis) in East Antarctica in 2004. Anomalous methane concentrations in bubbles suspended in lake ice and anomalous dissolved methane concentrations in lake water were frequently found. Methane concentrations in bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…In agreement with the findings of Sasaki et al (2009), we observed the opening of ebullition seeps throughout the thaw period, indicated by (1) open holes in ice at the locations of former ice-trapped bubbles, (2) rapid but short-lived (usually < 1 min, but occasionally > 10 min) streams of bubbles escaping from ice through puddles of water on the ice surface, and (3) the lack of gas escape from gas pockets in ice when punctured with an ice spear. We observed that seep sites with higher ebullition flux opened earlier, presumably due to thinner ice between encapsulated bubbles.…”
Section: Release Of Ice-trapped Bubblessupporting
confidence: 82%
See 1 more Smart Citation
“…In agreement with the findings of Sasaki et al (2009), we observed the opening of ebullition seeps throughout the thaw period, indicated by (1) open holes in ice at the locations of former ice-trapped bubbles, (2) rapid but short-lived (usually < 1 min, but occasionally > 10 min) streams of bubbles escaping from ice through puddles of water on the ice surface, and (3) the lack of gas escape from gas pockets in ice when punctured with an ice spear. We observed that seep sites with higher ebullition flux opened earlier, presumably due to thinner ice between encapsulated bubbles.…”
Section: Release Of Ice-trapped Bubblessupporting
confidence: 82%
“…The fraction of CH 4 that escapes to the atmosphere from seasonally ice-covered lakes depends on these biogeochemical processes. Previously, Sasaki et al (2009) measured the CH 4 concentration of bubbles trapped within lake ice in Antarctica and used aerial imaging to estimate the total volume of gas trapped before the ice melts. Elsewhere, others have measured dissolved CH 4 concentrations beneath winter lake ice or the CH 4 diffusion rate following ice-off to estimate net springtime emissions (e.g., Michmerhuizen et al, 1996;Phelps et al, 1998;Smith and Lewis, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Sasaki et al, (2009Sasaki et al, ( , 2010 reported that approximately two-times larger flux from frozen bubbles (ebullition) in lake ice than diffusive methane flux during the open water season is released in Syowa Oasis, east Antarctica. Bastiviken et al, (2004) also reported that estimated total methane flux (ebullition + diffusion + storage) from all Swedish lakes (95,762) was 105 Gg CH 4 yr -1 and that the flux corresponded to 5~10% of total flux from wetlands.…”
Section: Uncertainties In the Methods Used In This Studymentioning
confidence: 98%
“…One process is the exchange between air and the lake water surface caused by the chemical potential difference, and the other is direct efflux from bubbles suspended in lake ice early in the melting season. Sasaki et al [2009] estimated the flux of methane from ice bubbles in Syowa Oasis. Though another possible process was ebullition from unfrozen lakes, no bubbling was found, perhaps because of insufficient observations with a bubble trap.…”
Section: Introductionmentioning
confidence: 99%